Current strategies for diagnosis and treatment of Clostridium difficile-infection (literature review) - I. V. Nikolaeva; I. V. Shestakova; G. K. Murtazina (Acta Biomedica Scientifica, 2018)
The incidence and mortality rate of C. difficile infection (CDI) has increased remarkably over the last 10-20 years. CDI is a leading cause of healthcare-associated infections and antibiotic-associated diarrhoea. Increasing incidence and severity of CDI may be related with frequent antibiotic use and the emergence of a hypervirulent C. difficile strain. The epidemic strain NAP1 / BI / ribotype 027 is more resistant to antibiotics and produces more toxins and causes outbreaks around the world with increasing mortality and severity. Recent reports have documented that C. difficile infections occur among patients without traditional risk factors and the incidence of community-acquired CDI has increased. The clinical presentation of CDI ranging from the asymptomatic carrier to pseudomembranous colitis and toxic megacolon. The rate of recurrent CDI is 20-30 %. Early surgical consultation should be considered in all patients with severe or fulminant CDI. The preferred method for diagnosis CDI is stool testing using enzyme immunoassay (EIA) screening to look for glutamate dehydrogenase (GDH) antigen and toxins A and B. Metronidazole and vancomycin are recommended antibiotics for the treatment of CDI. Novel approaches include fidaxomicin therapy, monoclonal antibodies, and fecal microbiota transplantation. Fecal microbiota transplantation has shown relevant efficacy to overcome C. difficile infection and reduce it.